2011
DOI: 10.1038/ki.2010.526
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular-specific protein kinase C-β-induced insulin receptor substrate-1 dysfunction and insulin resistance in rat models of diabetes and obesity

Abstract: Insulin resistance has been associated with the progression of chronic kidney disease in both diabetes and obesity. This study characterizes insulin signaling in renal tubules and glomeruli in insulin resistant and diabetic states. Insulin-induced phosphorylation of insulin receptor substrate-1 (IRS1), Akt, endothelial nitric oxide (eNOS), and glycogen synthase kinase 3α (GSK3α) were selectively inhibited in the glomeruli but not in the renal tubules of both streptozotocin (STZ)-diabetic and Zucker fatty, insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
136
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(144 citation statements)
references
References 40 publications
8
136
0
Order By: Relevance
“…39 Treatment with the PKCb inhibitor Enzastaurin did not affect body weight in db/db mice when administered daily for two weeks beginning at eight weeks old (db/Enz; 50/mg/kg/d, PO; F 2,27 ¼ 12.87, p < 0.01; Figure 1(a)). Consistent with the reductions in body weight reported following administration of ruboxistaurin, a related PKCb inhibitor, 40 Enzastaurin reduced weight gain in Wt mice (two-week weight gain, grams; mean AE SEM, Wt/Veh ¼ 6.5 AE 1.1, Wt/Enz ¼ 2.2 AE 0.9). Because Enzastaurin reduced body weights beyond inclusion criteria in Wt mice, subsequent experiments did not include this treatment condition.…”
Section: Resultssupporting
confidence: 63%
“…39 Treatment with the PKCb inhibitor Enzastaurin did not affect body weight in db/db mice when administered daily for two weeks beginning at eight weeks old (db/Enz; 50/mg/kg/d, PO; F 2,27 ¼ 12.87, p < 0.01; Figure 1(a)). Consistent with the reductions in body weight reported following administration of ruboxistaurin, a related PKCb inhibitor, 40 Enzastaurin reduced weight gain in Wt mice (two-week weight gain, grams; mean AE SEM, Wt/Veh ¼ 6.5 AE 1.1, Wt/Enz ¼ 2.2 AE 0.9). Because Enzastaurin reduced body weights beyond inclusion criteria in Wt mice, subsequent experiments did not include this treatment condition.…”
Section: Resultssupporting
confidence: 63%
“…Another study has extended our under- standing of the insulin signaling in the renal endothelial cells. With the use of two rat models of diabetes, experiments showed that diabetes decreases insulin capability to trigger IRS-1/Akt/ eNOS phosphorylation in renal endothelial cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Coward and colleagues showed that podocytes are insulin-responsive cells. Insulin induced an acute increase in glucose uptake in cultured podocyte cell lines and in human podocytes ex vivo due to translocation of the glucose transporters GLUT-1 and GLUT-4 to the plasma membrane (6,23). Interestingly, renal disease similar to DN can be observed in patients with a genetic mutation of the insulin receptor (IR) (25).…”
mentioning
confidence: 99%
“…King and colleagues have recently clarified that the responses to insulin in rat models of diabetes and obesity -Zucker lean rats and control SD rats -are different between glomeruli and tubules [62]. In the glomeruli insulin-induced phosphorylation of IRS1, Akt, endothelial nitric oxide synthase (eNOS), and glycogen synthase kinase 3α (GSK3α) were all inhibited in glomeruli but not in the tubules.…”
Section: Insulin Effect In Animal Models: Difference Between Glomerulmentioning
confidence: 99%